Spectrophotometric analysis of tooth discolouration induced by mineral trioxide aggregate after final irrigation with sodium hypochlorite: An in vitro study. (9th March 2016) - Voveraityte, Valdone; Gleizniene, Simona; Lodiene, Greta; Grabliauskiene, Zivile; Machiulskiene, Vita
Abstract: The aim of this study was to evaluate specific chromatic alterations induced by white mineral trioxide aggregate after final irrigation with sodium hypochlorite. Sixty specimens were prepared mechanically and filled with mineral trioxide aggregate after different final irrigation protocols: Group 1 – distilled water, Group 2 – sodium hypochlorite followed by distilled water, Group 3 – sodium hypochlorite, only. Colour changes were recorded with a spectrophotometer at baseline, and then after 1, 2 and 4 months. The Commision Internationale de l'éclairage colour system was used and the total colour changes ΔE were calculated. In groups where sodium hypochlorite was used, parameter L* decreased significantly after the first month (Group 2 ( P < 0.006), Group 3 ( P < 0.009)). Group 3 demonstrated greater colour change ΔE than Group 1, after the first month ( P < 0.02). In conclusion, white mineral trioxide aggregate can lead to tooth discolouration by contact with sodium hypochlorite residues in dentinal tubules.